2019
DOI: 10.1007/s41465-019-00159-y
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Experiment Evaluating the Mindful Raisin Practice as a Method of Reducing Chocolate Consumption During and After a Mindless Activity

Abstract: The present study investigated the impact of the mindful raisin exercise on overeating during and after the experiment while controlling for wellbeing. One-hundred and twenty-eight participants were recruited and completed a questionnaire on wellbeing (i.e. depression, anxiety and stress) and state mindfulness. Participants were randomly allocated to either the mindful raisin exercise or a newspaper reading control condition. The State Mindfulness Scale was then completed again, and participants watched a neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 57 publications
4
32
2
Order By: Relevance
“…Our study has showed that there was no relationship between orthorexia and mindful eating, which was surprising as there is a clear attentional aspect that is more evident in following a speci c diet, and past research indicated that orthorexia nervosa was negatively correlated with mindfulness (Strahler, 2020). Our ndings go against all the studies conducted into mindfulness and mindful eating, and associations to healthier eating (Beshara, Hurchinson & Wilson, 2013;Dutt et al, 2018;Jordan et al, 2014;Mantzios, Egan & Asif, 2019) and protective values against the development of disordered eating (Moore et al, 2014). It was also surprising to nd that BMI and mindful eating were signi cantly positively associated to each other, suggesting that individuals with higher BMIs were more prone to eat mindfully (or vice versa).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Our study has showed that there was no relationship between orthorexia and mindful eating, which was surprising as there is a clear attentional aspect that is more evident in following a speci c diet, and past research indicated that orthorexia nervosa was negatively correlated with mindfulness (Strahler, 2020). Our ndings go against all the studies conducted into mindfulness and mindful eating, and associations to healthier eating (Beshara, Hurchinson & Wilson, 2013;Dutt et al, 2018;Jordan et al, 2014;Mantzios, Egan & Asif, 2019) and protective values against the development of disordered eating (Moore et al, 2014). It was also surprising to nd that BMI and mindful eating were signi cantly positively associated to each other, suggesting that individuals with higher BMIs were more prone to eat mindfully (or vice versa).…”
Section: Discussioncontrasting
confidence: 78%
“…Recent research proposed that mindful eating assists in the gradual change of external to internal motivations when eating, such as hunger, when participating in mindful eating interventions (Mantzios, Egan & Asif, 2019), promoting heathier eating behaviours (Mantzios & Wilson 2014, 2015aMantzios & Giannou, 2014;Zeros et al, 2021), including an increased intake of fruit and vegetables (Dutt et al, 2018;Gilbert & Waltz, 2010), and reductions in high sugar and energy dense food consumption (Mantzios, Skillett & Egan, 2020;Mason et al, 2016). Research has also found a negative association between mindful eating and motivations to eat palatable foods (Keyte et al, 2019;, fat and sugar consumption (Mantzios, Egan, Hussein, Keyte & Bahia, 2018b), and grazing (Mantzios, Egan, Bahia, Keyte & Hussein, 2018c).…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was based on the number of participants recruited in other similar studies (e.g. Macht and Mueller 2007;Mantzios et al 2019Mantzios et al , 2020. The mean BMI of the sample M = 22.30 (SD = 8.48) and age M = 24.23 (SD = 9.49), and their self-identified ethnicities were White or White British (n = 43), Black African or Caribbean (n = 18), Asian (n = 43), Middle Eastern (n = 5), Chinese (n = 5), mixed ethnicity (n = 5), and not specified (n = 1).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Furthermore, similar to classical music, mindfulness has shown to enhance the enjoyment of foods consumed (Arch et al, 2016;Hong et al, 2014). Research indicates that mindful attention can help reduce the temptations of consuming attractive, but unhealthy foods by viewing such simulations as mere mental events, and as a result assist in the gradual change of external to internal eating (Mantzios et al, 2019;Mantzios & Giannou, 2014;Marchiori & Papies, 2014). The majority of experimental studies that use mindfulness as a strategy in promoting healthier eating behaviours use body scan exercises or short audio recordings of mindful instructions (e.g., Jenkins & Tapper, 2014;Jordan et al, 2014).…”
mentioning
confidence: 99%